State of agricultural climate change adaptation policy in Nepal - Sova, Chase; Chaudhury, Abrar S. (2013)
This report is intended to complement the 2011 CCAFS publication “State of Climate Change Adaptation and Mitigation Efforts for Agriculture in Nepal” (Wang 2011). It provides relevant updates regarding the policies, projects, or initiatives introduced therein, and an assessment of the quickly evolving political scenario. Specifically, this document presents an objective look at 16 key policy/program/project documents within three principal thematic areas: (1) governance, (2) agriculture, and (3) climate change institutions in Nepal. Objectives and priorities for each of these documents are outlined, together with their evolution over time, intending to identify the temporal shifts in agricultural climate change policy direction in Nepal. Later sections address policy interplay between and within these thematic areas. The document aims to provide sufficient background to inform future CCAFS research in Nepal, particularly in the policy arena. The document is primarily addressed through an adaptation lens, as this research results from the Systemic Integrated Adaptation project, a CCAFS Theme 1 Adaptation to Progressive Climate Change initiative in collaboration with Oxford University’s Environmental Change Institute (ECI).